The many deaths of Laila Starr - V, Ram (Boom! Studios, 2022)
Humanity is on the verge of discovering immortality. The avatar of Death is cast down to Earth to live a mortal life in Mumbai as twenty-something Laila Starr. Will Laila take her chance to stop mankind from permanently altering the cycle of life?